Unveiling Thai University Students’ Perceptions of Plant-Based Foods: A Pathway to Promote Healthy Eating - Kulpavaropas, Supathida; Puathanawat, Nunnapan (Suan Sunandha Asian Social Science, 2024)
This study aims to 1) explore the perceptions of Thai university students regarding plant-based foods, 2) identify barriers hindering the adoption of plant-based foods, and 3) develop recommendations for strategic communication campaigns to promote plant-based food consumption. Employing mixed-methods research, this study utilizes questionnaires for quantitative data collection and content analysis for qualitative insights. The sample groups comprise 186 university students from an international college in the Salaya area, selected using random sampling. Quantitative data from questionnaires were analyzed using descriptive statistics, including percentages, means, and standard deviations. Qualitative data underwent content analysis to extract themes related to eating habits, perceptions, challenges, and misconceptions about plant-based foods. The research results found that 1) A significant majority of participants consume animal products frequently, despite acknowledging the health and environmental benefits of plant-based foods, indicating a gap between awareness and dietary practices. 2) The main barriers hindering the adoption of plant-based foods include taste preferences, cost concerns, and limited availability of appealing options, coupled with misconceptions that plant-based foods are "fake" or nutritionally insufficient. 3) Effective communication strategies emphasizing health benefits, environmental impact, ethical considerations, and addressing misconceptions could facilitate the transition towards plant-based foods among Thai university students. These insights are crucial for crafting targeted communication campaigns aimed at promoting a more sustainable and health-conscious future in Thailand.